Analisis Unjuk Kerja Plat Penyerap Corrugated-V pada Sistem Destilasi Surya Air Laut untuk Peningkatan Efisiensi Termal - Halim, Arfan (ReTII, 2025)
This was conducted to analyze the performance of a solar seawater distillation system equipped with a corrugated-V absorber plate at an angle of β = 20°. The experiment was conducted at the Workshop of Politeknik Sinar Mas Berau Coal to investigate the effect of absorber plate geometry on the absorptivity, useful energy, and distillation efficiency. The experimental results indicate that the absorber plate with a 20° angle achieved the highest average absorptivity value of 0.989, which was identified as the optimal configuration for the solar distillation system. The average useful energy produced during the distillation process was 683.11 kJ, with an average system efficiency of 16.53%. The maximum efficiency of 25.67% was recorded at 14:00 local time, and the total amount of distilled water produced was 300 ml. These findings demonstrate that the corrugated-V absorber plate with a 20° angle effectively enhances solar energy absorption and sustains the evaporation process, even under decreasing solar radiation intensity.